The Urgency of Land Banks in State Control of Land in Indonesia: Constitutional Study and Management Mechanisms - Mile, Moh Fachry H (CV. Rayyan Dwi Bharata, 2024)
The establishment of the Land Bank in Indonesia is a response to the complex issues surrounding land, including limited land availability, conflicting interests, and challenges in land law implementation. The Land Bank is established with the aim of improving land governance, supporting agrarian reform, and promoting the welfare of the people. However, there are several important issues related to the establishment of the Land Bank, including the lack of clarity regarding its philosophy, legal basis, and principles, as well as the urgency of its establishment. Additionally, the legal status and accountability of the Land Bank are not fully defined. In its implementation, the Land Bank utilizes resources from the state or regional budgets, as well as its own revenue and other legitimate sources. Operational activities of the Land Bank are planned on a medium-term and annual basis, and land utilization can be carried out through self-management or collaboration with other parties. The Land Bank also adheres to the nonprofit principle, where the revenue obtained is used for organizational development without distributing profits to the Land Bank's body. The establishment of the Land Bank in Indonesia has the potential to support economic development, but it also raises concerns regarding economic inequality and land injustice, particularly for economically disadvantaged groups. Therefore, proper monitoring and regulations are necessary to ensure that the Land Bank operates in line with its intended goals.